Dampak Media Sosial Terhadap Minat Karir Penerbangan : Studi Regresi Channel Youtube Vincent Raditya Pada Siswa Sekolah Penerbangan - Raysa, Alaya (Brand Communication, 2025)
The development of digital communication technology, particularly social media, has transformed how the younger generation accesses information and makes career choices. YouTube, as one of the largest platforms, provides educational content that influences viewers' interests and motivation, including in the fields of education and professional careers. This study analyzes the impact of educational content from the YouTube channel Vincent Raditya on the interest of aviation school students in pursuing careers in the aviation field. Vincent Raditya, a commercial pilot and content creator, presents aviation material in an engaging and easy-to-understand manner. The research employs a quantitative approach through surveys distributed to students at Angkasa Aviation Academy (AAA). Data analysis includes validity, reliability, normality tests, and simple linear regression. The findings reveal a positive and significant influence between the consumption of Vincent Raditya’s educational content and students’ interest in becoming pilots. Factors such as appealing visuals, communicative language, and shared practical experiences are key elements that drive students’ motivation to learn. This study contributes to the development of digital communication strategies in aviation education institutions and serves as a guide for content creators to produce effective and engaging educational material for the younger generation in the digital era.